Religious Peace building, the Problems, and Potentials Now and in the Foreseeable Federal Republic of Nepal - Suvedi, Mukti (Contemporary Research: An Interdisciplinary Academic Journal, 2021)
Introduction: There is debate whether most Nepali people still want Nepal to be a Hindu state. A significant number of opinions wish to see the country as secular, where people are respected with dignity without any discrimination where people can profess, practice, and protect their religions, whichever religion it may be. Methods: This paper is based on public opinion surveys through interviews and discussions with100 individuals, including key informant interviews with 25 religious leaders from different religions conducted between September 20019 and February 2020 and secondary data from various literature reviews. Results: The paper's finding reveals that the public's preference toward the Hindu state is not accepted in all sub-national levels; a secular state preference is evident in some of the sub-national levels, which cannot be undervalued. The mindsets of most of the elder populations interviewed still want Nepal to be the only Hindu state in the world, whereas the active young-age (youth) population is more inclusive and is happy with the secular nation. Conclusion: Understanding and implementing inclusive secular policies and practicing the preexistence principles of religious freedom by the political parties and incorporating the same in all government, semi-government and private sectors will ensure a secular and peaceful Nepal. Government authorities and other bureaucrats becoming more sensitive towards religious issues will create space for promoting peace.